PENGARUH TALENT MANAGEMENT DAN KNOWLEDGE SHARING TERHADAP KINERJA KARYAWAN DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIASI (Studi pada Rumah Sakit Umum Bandung di Kota Medan) - Agustina Handayani; Survival; Ana Sopanah; Hanif Rani Iswari; Choirul Anam (MANAJEMEN DEWANTARA, 2026)
This study aims to determine the influence of Talent Management and knowledge sharing on employee performance with Employee Engagement as a mediating variable. The research model used in this study is variance-based Structural Equation Modeling (SEM), namely Partial Least Square (PLS). The population used in this study consisted of employees at Rumah Sakit Umum Bandung in Medan City. The number of samples was 54 respondents. A Likert scale was used to measure respondents’ statements in the questionnaire with alternative answers consisting of strongly disagree, disagree, neutral, agree, and strongly agree. To test the hypotheses, the researcher analyzed the data using the SEM-PLS model with SmartPLS version 3 software. The results of the study indicate that Talent Management has a positive and significant effect on employee performance. Knowledge Sharing has a positive and significant effect on employee performance. Talent Management has a positive and significant effect on employee engagement. Knowledge Sharing has a positive and significant effect on employee engagement. Employee Engagement has a positive but not significant effect on employee performance. Employee Engagement is unable to mediate the influence of Talent Management on Employee Performance. Employee Engagement is also unable to mediate the influence of Knowledge Sharing on Employee Performance